Metabolic effects of pesticide effluents on Nicotiana tabacum and Vigna radiata plants - Mishra, Kumkum; Sanwal, Eera; Tandon, PK; Gupta, Kiran (International Journal of Environment, 2015)
Some important metabolic parameters were investigated in relation to various doses of pesticide effluents in two economically plants viz. Nicotiana and Vigna plants. Increasing doses of pesticide effluents caused decrease in both sugar and protein concentration almost similarly in both plants. However, activities of enzymes, catalase, peroxidase and MDA content were found to be stimulated by higher doses of pesticide factory effluents in both the plants. Protein and sugar content decreased at all doses in Nicotiana tabacum however there were increase in enzymatic activity like catalase and peroxidase. MDA content was also increased in same plant. On the other hand Vigna radiata showed inducing nature of protein content at lower concentration (25%) and thereafter inhibit at all doses while sugar content decreased at all concentrations. Enzymatic activity viz. catalase and peroxidase showed promoting nature at all concentrations. MDA content also increased at all concentrations. Thus it can be concluded that but for small differences in almost all the metabolic parameters towards their response towards pesticide industry effluent both the studied plants i.e. Nicotiana and Vigna were found to be quite susceptible towards pesticide effluents. DOI: http://dx.doi.org/10.3126/ije.v4i2.12628 International Journal of Environment Vol.4(2) 2015: 87-94